Iridium oxide catalyst with dendritic pore structure, preparation method and application of iridium oxide catalyst in proton exchange membrane water electrolysis technology

By preparing an iridium oxide catalyst with dendritic pore structure, the problem of large amount of iridium and difficult to maintain catalytic performance in the membrane electrode is solved, and the effect of high-efficiency oxygen evolution catalytic reaction under low iridium load is achieved.

CN119706982AActive Publication Date: 2025-03-28JILIN UNIVERSITY +1

Patent Information

Application Number
CN202411889282.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The large amount of iridium is used in existing membrane electrodes, which leads to the contradiction between supply shortage and surge in demand, and it is difficult for new iridium-based materials to maintain high catalytic performance in PEM electrolytic cells.

Method used

Using an iridium oxide catalyst with a dendritic pore structure, a pore reamer and an initiator are added by combining an iridium source with a template, and a pore reamer and an initiator are obtained after heating and stirring.

Benefits of technology

The catalyst provides more active sites, and its rich pore structure improves the mass transport capacity of the catalyst, overcomes the diffusion limitation of non-porous materials, exhibits high activity and stability under low iridium loading, and realizes high-efficiency oxygen evolution catalytic reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706982A_ABST
    Figure CN119706982A_ABST
Patent Text Reader

Abstract

The invention discloses an iridium oxide catalyst with a dendritic pore structure, a preparation method and application of the iridium oxide catalyst in a proton exchange membrane water electrolysis technology, and belongs to the technical field of water electrolysis. The preparation method comprises the following steps: dissolving an iridium source in water, adding a mixed template agent, dissolving, adding a pore-enlarging agent, and uniformly mixing to obtain a uniform emulsion; and adding an initiator for reaction, after the reaction is finished, centrifugally cleaning for 3-5 times by using a mixed solution of water and absolute ethyl alcohol in a volume ratio of 1: 1, washing off the template agent, and drying to obtain the iridium oxide catalyst with the dendritic pore structure. Compared with commercial iridium oxide catalyst nanoparticles, the iridium oxide catalyst with the dendritic pore structure prepared by the invention provides more active sites, and meanwhile, the mass transmission capability of the catalyst is remarkably improved due to the abundant pore structure, and the diffusion limitation existing in a non-porous material is overcome; therefore, the catalyst shows relatively high activity and stability in PEM electrolyzed water oxygen evolution reaction under low iridium loading, and efficient oxygen evolution catalytic reaction is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis, and in particular relates to an iridium oxide catalyst with a dendritic pore structure, a preparation method and application thereof in proton exchange membrane water electrolysis technology. Background Art

[0002] Hydrogen (green hydrogen) produced by electrolysis of water from renewable energy represented by photovoltaics and wind power is considered to be a key carrier for the success of energy transformation and has become the focus of accumulation of strength in various countries. Proton exchange membrane (PEM) water electrolysis technology can convert intermittent renewable electricity into high-purity green hydrogen, and has become a key technology for my country's energy transformation. The core component of the PEM electrolyzer, the membrane electrode, gives it advantages such as high energy conversion efficiency, high current density and compact design. Given the large amount of iridium used in commercial membrane electrodes, the demand for iridium will increase significantly when it is applied on a large scale. However, the annual output of iridium is limited (<10 tons) and the price is high, making the contradiction between supply shortages and surging demand increasingly prominent. Therefore, reducing the amount of iridium in the membrane electrode while maintaining high catalytic performance is crucial for the widespread application of PEM water electrolysis technology.

[0003] In order to reduce the amount of iridium in the membrane electrode, the most important thing is to develop anode catalysts with higher catalytic performance. However, although a variety of new iridium-based materials developed in recent years have shown excellent catalytic activity in the three-electrode test of liquid electrolyzers in the laboratory, their high performance is difficult to reproduce in PEM electrolyzers. This is mainly due to the difference between the idealized three-electrode test conditions and the complex operating environment of the membrane electrode. When the operating circuit density of the PEM electrolyzer reaches the ampere level, the structural stability of the anode catalyst and the mass transfer process of the anode catalyst layer will face greater challenges. For example, in commercial PEM electrolyzers, iridium oxide catalyst nanoparticles are easy to aggregate, resulting in high loading (iridium loading is usually not less than 2 mg cm -2 ), the utilization rate of active sites in the membrane electrode is low, and the transport resistance of water and oxygen is increased. Therefore, it is imperative to design and synthesize iridium oxide catalysts with both high catalytic activity and excellent mass transfer performance. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention aims to provide an iridium oxide catalyst with a dendritic pore structure, a preparation method and its application in proton exchange membrane water electrolysis technology.

[0005] The invention discloses a method for preparing an iridium oxide catalyst with a dendritic pore structure, which comprises the following steps: dissolving an iridium source in water, adding a mixed template agent, adding a pore-enlarging agent after dissolution, and mixing uniformly to obtain a uniform emulsion; adding an initiator to carry out a reaction, and after the reaction is completed, washing the mixture 3 to 5 times by centrifugation with a mixed solution of water and anhydrous ethanol in a volume ratio of 1:1, washing the template agent off, and drying to obtain the iridium oxide catalyst with a dendritic pore structure; the obtained iridium oxide catalyst is a porous nanosphere or ellipsoid structure with a particle size of 100 to 400 nm; the iridium oxide catalyst has an open dendritic pore structure with a pore size of 10 to 30 nm.

[0006] In the above method, the iridium source is one or a mixture of chloroiridic acid, iridium trichloride, iridium tetrachloride, potassium chloroiridate, and sodium chloroiridate;

[0007] In the above method, the mixed template agent is a mixture of EO-PO-EO block copolymer and quaternary ammonium salt surfactant, and the EO-PO-EO block copolymer is F127 (EO 106 -PO 70 -EO 106 )、F108(EO 132 -PO 50 -EO 132 )、P123(EO 20 -PO 70 -EO 20 ), the quaternary ammonium salt surfactant is a mixture of one or more of dodecyltrimethylammonium chloride and dodecyltrimethylammonium bromide;

[0008] In the above method, the pore-enlarging agent is one or a mixture of benzene, toluene and mesitylene;

[0009] In the above method, the initiator is one or a mixture of 3-8% by mass of ammonia water, sodium hydroxide, sodium borohydride;

[0010] In the above method, in the mixed solution, the mass ratio of iridium source, water, EO-PO-EO block copolymer, quaternary ammonium salt surfactant, pore expander and initiator is 1:100-500:0.5-3:0.1-1:1-50:0.05-0.5;

[0011] In the above method, the raw materials are mixed uniformly by ultrasonication for 5 to 10 minutes or stirring for 20 to 40 minutes;

[0012] In the above method, the reaction temperature is 50 to 80° C. and the reaction time is 6 to 10 hours.

[0013] The iridium oxide catalyst with a dendritic pore structure described in the present invention is prepared by the above preparation method.

[0014] The iridium oxide catalyst with a dendritic pore structure described in the present invention can be applied in the proton exchange membrane water electrolysis technology.

[0015] Beneficial effects of the present invention:

[0016] The present invention adopts a one-pot method to fully combine the iridium source and the template agent in an aqueous solution, and then adds a weak base as an initiator, and obtains an iridium oxide catalyst with a dendritic pore structure by simple heating and stirring. The preparation method of the present invention is simple and easy, has a high yield, a safe and green operation process, and a flexible selection of the precursor metal iridium source, which is conducive to industrial production; at the same time, the present invention has a reference value for the preparation of other mesoporous metal oxides. The iridium oxide catalyst with a dendritic pore structure prepared by the present invention provides more active sites than commercial iridium oxide catalyst nanoparticles, and the rich pore structure significantly improves the mass transfer capacity of the catalyst, overcomes the diffusion limitation existing in non-porous materials, and therefore exhibits higher activity and stability in the PEM water electrolysis oxygen evolution reaction at a low iridium loading, achieving an efficient oxygen evolution catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of the iridium oxide catalyst having a dendritic pore structure prepared in Example 1 of the present invention;

[0018] Figure 2 TEM image of the iridium oxide catalyst having a dendritic pore structure prepared in Example 1 of the present invention;

[0019] Figure 3 This is a diagram showing the catalytic performance of the iridium oxide catalyst with a dendritic pore structure prepared in Example 1 of the present invention for use in a PEM water electrolysis membrane electrode device;

[0020] Figure 4 This is a diagram showing the catalytic stability of the iridium oxide catalyst with a dendritic pore structure prepared in Example 1 of the present invention when used in a PEM water electrolysis membrane electrode device. DETAILED DESCRIPTION

[0021] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.

[0022] It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0023] The process condition values ​​in the following examples are exemplary, and the range of values ​​is as shown in the above invention content. For process parameters not specifically noted, conventional techniques can be used. Unless otherwise specified, the reagents and instruments used in the technical solutions provided by the present invention can be purchased from conventional channels or the market.

[0024] Example 1

[0025] This embodiment prepares an iridium oxide catalyst particle with a dendritic pore structure, and the specific method is as follows: 0.6g of iridium trichloride is dissolved in 100mL of water, and after the iridium source is dissolved, 0.5g of the template block copolymer F127 and 0.1g of hexadecyltrimethylammonium bromide are added, and after the template is dissolved, 3mL of the pore-enlarging agent mesitylene is added, and ultrasonication is performed for 5 minutes or stirring is performed for 30 minutes to form a uniform emulsion. Then the obtained emulsion is heated and stirred at 70°C, 3mL of ammonia water with a mass fraction of 5% is added dropwise, and the heating and stirring reaction is continued for 8 hours. After the reaction is completed, the solid product is collected, washed 3 times with a mixed solution of water and ethanol in a volume ratio of 1:1, the product is collected after the template is washed off, and the iridium oxide catalyst particles with a dendritic pore structure are obtained after drying at 80°C, the product mass is 0.38g, wherein the iridium content is 84%, and it is dried and stored at room temperature.

[0026] The synthesized porous iridium oxide catalyst was characterized and tested. Figure 1 This is a scanning electron microscope (SEM) image of the catalyst, from which it can be seen that the catalyst is approximately spherical particles with a particle size of 100 to 300 nm and a large number of mesopores on the surface. Figure 2 This is a transmission electron microscope (TEM) image of an iridium oxide catalyst. In the image, it can be found that the iridium oxide catalyst has a radially open dendritic pore structure. The pores penetrate deep into the interior of the iridium oxide catalyst particles, and the pore diameter is between 10 and 30 nm.

[0027] The prepared porous iridium oxide catalyst with a dendritic pore structure is used in a PEM water electrolysis device as a catalyst for oxygen evolution reaction on the anode side of the membrane electrode, and a commercial platinum-carbon catalyst is used as a catalyst for hydrogen evolution reaction on the cathode side. The catalysts of the cathode and cathode are sprayed on both sides of the proton exchange membrane by a catalyst coating membrane preparation method, and then assembled into a PEM device with a gas diffusion layer, a bipolar plate, a sealing ring, etc. The membrane electrode preparation, PEM electrolyzer assembly and specific testing process are as shown in the reference (Angew. Chem. Int. Ed. 2024, e202415032.). The test results are as follows Figure 3 As shown, the iridium loading at the anode is only 0.50 mg cm -2 The catalytic performance can reach 3.82A cm at 80℃ -2 @2V, indicating that the catalyst has good membrane electrode device performance and is -2 The catalytic stability is more than 200 h in a large current density range. Figure 4 ).

[0028] In summary, the iridium oxide catalyst with a dendritic pore structure prepared in this embodiment can be well adapted to the OER catalyst in an acidic environment. The material exhibits very high catalytic activity and stability in the membrane electrode water electrolysis test, and shows great application potential in PEM water electrolysis devices.

[0029] Example 2

[0030] This example is the same as Example 1, except that the iridium source is changed to 0.4 g potassium chloroiridate, the reaction temperature is changed to 60°C, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure is still obtained, with a particle diameter of about 100 nm, a pore size of about 20 nm, and an iridium loading of 0.44 mg cm at the anode. -2 The catalytic performance can reach 3.69A cm at 80℃ -2 @2V.

[0031] Example 3

[0032] This example is the same as Example 1, except that the initiator is changed to 5 mL of 5% ammonia water, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure is still obtained. The particle diameter is about 80 nm, the pore size is about 10 nm, and the iridium loading at the anode is 0.51 mg cm -2 The catalytic performance can reach 3.71A cm at 80℃ -2 @2V.

[0033] Example 4

[0034] This example is the same as Example 1, except that the initiator is changed to 0.1 g sodium borohydride, the reaction temperature is changed to 60°C, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure is still obtained. The particle diameter is about 100 nm, the pore size is about 15 nm, and the iridium loading at the anode is 0.63 mg cm -2 The catalytic performance can reach 3.72A cm at 80℃ -2 @2V.

[0035] Example 5

[0036] This example is the same as Example 1, except that the template agent is changed to 1g of block copolymer F127 and 0.2g of hexadecyltrimethylammonium bromide, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure can still be obtained. The particle diameter is about 100nm, the pore size is about 20nm, and the iridium loading at the anode is 0.52mg cm -2 The catalytic performance can reach 3.70A cm at 80℃ -2 @2V.

[0037] Example 6

[0038] This example is the same as Example 1, except that the template agent is changed to 0.5 g of block copolymer P123 and 0.1 g of dodecyltrimethylammonium bromide. Other synthesis conditions remain unchanged, and an iridium oxide catalyst with a dendritic pore structure is still obtained. The particle diameter is about 200 nm, the pore size is about 30 nm, and the iridium loading at the anode is 0.48 mg cm -2 The catalytic performance can reach 3.73Acm at 80℃ -2 @2V.

[0039] Example 7

[0040] This example is the same as Example 1, except that the template agent is changed to 0.5 g of block copolymer F127 and 0.1 g of hexadecyltrimethylammonium chloride, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure is still obtained. The particle diameter is about 150 nm, the pore size is about 25 nm, and the iridium loading at the anode is 0.55 mg cm -2 The catalytic performance can reach 3.80Acm at 80℃ -2 @2V.

[0041] Example 8

[0042] This example is the same as Example 1, except that the template agent is changed to 0.5 g of block copolymer F127 and 0.1 g of dodecyl trimethyl ammonium chloride, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure can still be obtained. The particle diameter is about 150 nm, the pore size is about 20 nm, and the iridium loading at the anode is 0.43 mg cm-2 The catalytic performance can reach 3.77Acm at 80℃ -2 @2V.

[0043] Example 9

[0044] This example is the same as Example 1, except that the template agent is changed to 0.5 g of block copolymer F127 and 0.15 g of octadecyltrimethylammonium bromide, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure can still be obtained. The particle diameter is about 200 nm, the pore size is about 25 nm, and the iridium loading at the anode is 0.56 mg cm -2 The catalytic performance can reach 3.72Acm at 80℃ -2 @2V.

[0045] Example 10

[0046] This example is the same as Example 1, except that the pore-enlarging agent is changed to 5 mL of mesitylene, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure is still obtained. The particle diameter is about 200 nm, the pore size is about 30 nm, and the iridium loading at the anode is 0.51 mg cm -2 The catalytic performance can reach 3.79Acm at 80℃ -2 @2V.

[0047] Embodiment 11

[0048] This example is the same as Example 1, except that the pore-enlarging agent is changed to 3 mL of benzene, and other synthesis conditions remain unchanged. An iridium oxide catalyst with a dendritic pore structure is still obtained. The particle diameter is about 200 nm, the pore size is about 20 nm, and the iridium loading at the anode is 0.47 mg cm -2 The catalytic performance can reach 3.75Acm at 80℃ -2 @2V.

Claims

1. A method for preparing an iridium oxide catalyst having a dendritic pore structure, characterized in that: The method comprises the following steps: dissolving an iridium source in water, adding a mixed template agent, adding a pore expander after the iridium source is dissolved, and mixing the mixture to obtain a uniform emulsion; adding an initiator to react, and after the reaction is completed, washing the mixture 3 to 5 times by centrifugation with a mixed solution of water and anhydrous ethanol in a volume ratio of 1:1, washing the template agent off, and drying the mixture to obtain the iridium oxide catalyst with a dendritic pore structure; the obtained iridium oxide catalyst is a porous nanosphere or ellipsoid structure with a particle size of 100 to 400 nm; the iridium oxide catalyst has an open dendritic pore structure with a pore size of 10 to 30 nm.

2. A method for preparing an iridium oxide catalyst having a dendritic pore structure as claimed in claim 1, characterized in that: The iridium source is one of chloroiridic acid, iridium trichloride, iridium tetrachloride, potassium chloroiridate, sodium chloroiridate, or a mixture of several thereof.

3. A method for preparing an iridium oxide catalyst having a dendritic pore structure as claimed in claim 1, characterized in that: The mixed template agent is a mixture of EO-PO-EO block copolymer and quaternary ammonium salt surfactant, and the EO-PO-EO block copolymer is F127 (EO 106 -PO 70 -EO 106 )、F108(EO 132 -PO 50 -EO 132 )、P123(EO 20 -PO 70 -EO 20 ), and the quaternary ammonium salt surfactant is a mixture of one or more of dodecyltrimethylammonium chloride and dodecyltrimethylammonium bromide.

4. A method for preparing an iridium oxide catalyst having a dendritic pore structure as claimed in claim 1, characterized in that: The pore expanding agent is one of benzene, toluene and mesitylene or a mixture of several of them.

5. The method for preparing an iridium oxide catalyst having a dendritic pore structure as claimed in claim 1, characterized in that: The initiator is one or a mixture of 3-8% by mass of ammonia water, sodium hydroxide and sodium borohydride.

6. The method for preparing an iridium oxide catalyst having a dendritic pore structure according to claim 1, characterized in that: The raw materials are mixed evenly by ultrasonic treatment for 5 to 10 minutes or stirring for 20 to 40 minutes.

7. The method for preparing an iridium oxide catalyst having a dendritic pore structure according to claim 1, characterized in that: The reaction temperature is 50 to 80°C, and the reaction time is 6 to 10 hours.

8. The method for preparing an iridium oxide catalyst having a dendritic pore structure as claimed in claim 3, characterized in that: In the mixed solution, the mass ratio of the iridium source, water, EO-PO-EO block copolymer, quaternary ammonium salt surfactant, pore expander and initiator is 1:100-500:0.5-3:0.1-1:1-50:0.05-0.

5.

9. An iridium oxide catalyst having a dendritic pore structure, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the iridium oxide catalyst having a dendritic pore structure as claimed in claim 9 in proton exchange membrane water electrolysis technology.

Citation Information

Patent Citations

  • Method for preparing platinum iridium ruthenium composite nanoparticles by microemulsion method

    CN109382097A

  • Preparation and application of a dendritic mesoporous silica / iridium dioxide composite nanometer enzyme

    CN110180596A

  • Preparation method of platinum-ruthenium-titanium composite nanoparticles by using microemulsion method

    CN111530457A

  • Integrated membrane electrode with ultralow noble metal loading capacity, and preparation method and application thereof

    CN113285107A

  • Metastable phase porous iridium oxide catalyst, preparation method and application of catalyst in proton exchange membrane water electrolysis technology

    CN116377481A

Cited By

  • Pine branch-shaped fractal ruthenium oxide nano material as well as preparation method and application thereof

    CN121110076A